1993
DOI: 10.1159/000177766
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein Cholesterol Concentrations and Postheparin Hepatic and Lipoprotein Lipases in Obesity: Relationships with Plasma Insulin Levels

Abstract: The concentration of high-density lipoprotein (HDL) cholesterol in patients with severe obesity is generally subnormal. The exact mechanism linking obesity with reduced levels of HDL cholesterol remains unclear. In this study we evaluated the postheparin plasma lipolytic enzymes lipoprotein lipase (LPL) and hepatic lipase (HL) in a group of 24 obese women compared with controls and analyzed the interrelationships between insulin, postheparin lipolytic enzymes and HDL subfractions. Total HDL cholesterol was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Our findings may help to explain observations made in several previous studies. These previous studies have demonstrated correlations either between elevated plasma hepatic lipase activity (11)(12)(13)17) or hypoadiponectinemia (8 -10,18) with parameters of the insulin resistance (metabolic) syndrome, such as obesity, type 2 diabetes, hypertriglyceridemia, and low HDL cholesterol. Hepatic lipase is regulated predominantly by cell cholesterol content, steroids, and thyroid hormones (3).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings may help to explain observations made in several previous studies. These previous studies have demonstrated correlations either between elevated plasma hepatic lipase activity (11)(12)(13)17) or hypoadiponectinemia (8 -10,18) with parameters of the insulin resistance (metabolic) syndrome, such as obesity, type 2 diabetes, hypertriglyceridemia, and low HDL cholesterol. Hepatic lipase is regulated predominantly by cell cholesterol content, steroids, and thyroid hormones (3).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The hepatic lipase regulatory interactions with insulin are, however, not clear-cut, and hepatic lipase responsiveness to insulin is controversial. Most studies in patients with chronic hy- perinsulinemia show higher hepatic lipase activities than in control subjects (11,13,17,19), whereas others report either reduced hepatic lipase activity in type 1 diabetic patients (20) or upregulated hepatic lipase activity by insulin treatment in general (21,22). Therefore, hepatic lipase activity appears to be not clearly upregulated by insulin, and the precise mechanism that links hepatic lipase activity to insulin resistance remains unclear.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…33 Elevated insulin concentrations may also influence the activity of hepatic lipase, and insulin resistance may affect lipoprotein lipase, both of which are involved in the metabolism of HDL cholesterol. 34,35 Reduced lipoprotein lipase and increased hepatic lipase activity result in decreased maturation and increased catabolism of HDL cholesterol, respectively. Rocchini 36 has studied the relationship of insulin sensitivity to blood pressure in obese adolescents and found that increased circulating levels of insulin are related to blood pressure elevation.…”
Section: Discussionmentioning
confidence: 99%
“…Men have a higher HL activity than women because of a number of endogenous factors, such as central adiposity and sex steroid hormones (14,15,26,39,40). Recently, Carr et al (41) also demonstrated that intra-abdominal fat is a major component of the sex difference in HL activity.…”
Section: Hl Activity In Type 2 Diabetesmentioning
confidence: 99%